Drosophila DDX3/Belle Exerts Its Function Outside of the Wnt/Wingless Signaling Pathway. - Jenny, F.H.; Basler, K. (PLoS ONE, 2016)
The helicases human DDX3 and Drosophila Belle (Bel) are part of a well-defined subfamily of the DEAD-box helicases. Individual subfamily-members perform a myriad of functions in nuclear and cytosolic RNA metabolism. It has also been reported that DDX3X is involved in cell signaling, including IFN-? and IFN-? inducing pathways upon viral infection as well as in Wnt signaling. Here we used a collection of EMS-induced bel alleles recovered from a Wingless (Wg) suppressor screen to analyze the role of the Drosophila homolog of DDX3 in Wg/Wnt signaling. These EMS alleles, as well as a P-element induced null allele and RNAi-mediated knock down of bel, all suppressed the phenotype of ectopic Wg signaling in the eye. However, they did not affect the expression of known Wg target genes like senseless, Distalless or wingful/Notum. Ectopic Wg signaling in eye imaginal discs induces apoptosis by increasing grim expression. Mutations in bel revert grim expression to wild-type levels. Together, these results indicate that Bel does not function as a core component in the Drosophila Wg pathway, and that mutations affecting its helicase function suppress the effects of ectopic Wg signaling downstream of the canonical pathway.